Morphometric Analysis of Wadi Hasab Basin in Al-Najaf Governorate, Southwest of Iraq, Using Remote Sensing and GIS Techniques - Ali, Maryam H.; Mohammed, Faisel G.; Al-Saady, Younus I. (Iraqi Journal of Science, 2025)
Quantitative analysis of morphometric drainage systems is crucial for understanding hydrological and environmental interactions of watersheds. This study uses geospatial techniques to analyze the morphometric characteristics of watersheds, relying on ALOS World 3D DEM and topographic maps of Iraq. Key features identified include main basins, sub-basins, slopes, drainage networks, topographical patterns, flow sequences, and flow lengths. ArcGIS Pro V.3.0.2 was used to determine these characteristics. The analysis includes hydrological processes like runoff frequency, bifurcation ratio, circularity ratio, and surface runoff length. The study aims to understand how these parameters affect the regional morphological landscape and the role of watersheds in the water cycle. Quantitative measurements provide insights into watersheds’ shape, size, and hydrological status. The Hasab basin is a seventh-order basin, consisting of seven sub-basins that form an almost rectangular. Hypsometric analysis reveals geomorphological characteristics and basin maturity. The Hasab basin and most sub-basins are in the late youth or maturity stage, except for SB2 and SB4, which are in the old stage. The morphometric parameters indicate that geological and geomorphological structures significantly influence the drainage network type and basin shape.